Pelaksanaan Publikasi Informasi Melalui Website Sekolah di Sekolah Islam Terpadu (SIT) Izzuddin Palembang - Hasbi, Muhammad; Wulandari, Fitri; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze The Implementation of Information Publication through the School Website at the Integrated Islamic School (SIT) Izzuddin Palembang. The research uses a qualitative method with a descriptive approach. There are 11 informants, with data collected through interviews, observations, and documentation. Data analysis techniques include data collection, presentation, verification, and drawing conclusions. Data validity was tested using triangulation. The results and discussion show that the implementation of information publication through the school website at the Integrated Islamic School (SIT) Izzuddin Palembang has been carried out well, through 5 stages, namely information collection, information processing, information analysis, presentation and dissemination of information and information storage.